Comparing the cost-effectiveness of four novel risk markers for screening asymptomatic individuals to prevent cardiovascular disease (CVD) in the US population. (15th January 2016) - van Kempen, Bob J.H.; Ferket, Bart S.; Steyerberg, Ewout W.; Max, Wendy; Myriam Hunink, M.G.; Fleischmann, Kirsten E.
Abstract: Background: High sensitivity CRP (hsCRP), coronary artery calcification on CT (CT calcium), carotid artery intima media thickness on ultrasound (cIMT) and ankle-brachial index (ABI) improve prediction of cardiovascular disease (CVD) risk, but the benefit of screening with these novel risk markers in the U.S. population is unclear. Methods and results: A microsimulation model evaluating lifelong cost-effectiveness for individuals aged 40–85 at intermediate risk of CVD, using 2003–2004 NHANES-III (N = 3736), Framingham Heart Study, U.S. Vital Statistics, meta-analyses of independent predictive effects of the four novel risk markers and treatment effects was constructed. Using both an intention-to-treat (assumes adherence < 100% and incorporates disutility from taking daily medications) and an as-treated (100% adherence and no disutility) analysis, quality adjusted life years (QALYs), lifetime costs (2014 US $), and incremental cost-effectiveness ratios (ICER in $/QALY gained) of screening with hsCRP, CT coronary calcium, cIMT and ABI were established compared with current practice, full adherence to current guidelines, and ubiquitous statin therapy. In the intention-to-treat analysis in men, screening with CT calcium was cost effective ($32, 900/QALY) compared with current practice. In women, screening with hsCRP was cost effective ($32, 467/QALY). In the as-treated analysis, statin therapy was both more effective and less costly than all other strategies for both men and women. Conclusions: When a substantial disutility from taking daily medication is assumed, screening men with CT coronary calcium is likely to be cost-effective whereas screening with hsCRP has value in women. The individual perceived disutility for taking daily medication should play a key role in the decision.